1999
DOI: 10.1021/ja991603h
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Covalent Intermediate in the Viral Neuraminidase Reaction? A Hybrid Potential Free-Energy Study

Abstract: The neuraminidase from the influenza virus is essential for maintaining viral infectivity as it aids in the transmission of the virus between cells. Although there are large variations in the amino acid sequences of neuraminidases from different influenza strains, there are several amino acids in the active site region of the protein that are strictly conserved. This has raised hopes that a single neuraminidase inhibitor and, hence a drug, can be found that is effective against all influenza strains. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…65,66,70,71,79,98,106,157 Enzyme applications have been based on Warshel's quantized classical path (QCP) algorithm. 66 This is similar in many respects to MQCMD, but it is easier to quantize more than one atom.…”
Section: Quantized Classical Path Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…65,66,70,71,79,98,106,157 Enzyme applications have been based on Warshel's quantized classical path (QCP) algorithm. 66 This is similar in many respects to MQCMD, but it is easier to quantize more than one atom.…”
Section: Quantized Classical Path Methodsmentioning
confidence: 99%
“…The concept of potential of mean force 98,167,205,[387][388][389][390][391][392][393][394][395][396][397][398][399][400][401] (PMF) plays an important role in condensed-phase TST. The PMF is usually computed by classical mechanics as a function of a single coordinate, called the distinguished coordinate and here denoted z.…”
Section: Ensemble-averaged Variational Transition State Theory With Mmentioning
confidence: 99%
“…Tests performed in other systems indicated that results obtained within this scheme are equivalent to results obtained without truncation. 46,44 All simulations and free energy calculations were performed with the DYNAMO library.…”
Section: E Simulation Detailsmentioning
confidence: 99%
“…59 for details), but they are computationally expensive and so further applications of this technique to enzyme reactions have been limited, although a study of a hydrogen transfer in the reaction catalyzed by the flu virus neuraminidase has also been published. 154 A number of techniques, other than path-integral methods, have been used to investigate quantum dynamical effects in enzyme reactions. Thus, in two recent articles, Alhambra et al employed semiempirical QM/MM potentials in conjunction with semiclassical variational TST to calculate the rates and the kinetic isotope effects (KIEs) for the proton transfer in the yeast enolase reaction 155 and the hydride transfer in liver alcohol dehydrogenase (LADH).…”
Section: Quantum Effectsmentioning
confidence: 99%